Future Smart Cooking Machine System Design - Alif Ahmad Syamsudduha; Dyah Pratiwi; Ardhani Reswari Yudistari; Jonathan Hindharta; Dewi Agushinta R. (Universitas Ahmad Dahlan, 2013)
There are many tools make human task get easier. Cooking has become a basic necessity for human beings, since food is one of basic human needs. Until now, the cooking equipment being used is still a hand tool. However everyone has slightly high activity. The presence of cooking tools that can do the cooking work by itself is now necessary. Future smart cooking machine is an artificial intelligence machine that can do cooking work automatically. With this system design, the time is minimized and the ease of work is expected to be achieved. The development of this system is carried out with system development life cycle (SDLC) methods. Prototyping method used in this system is a throw-away prototyping approach. At the end of this research there will be produced a cooking machine system design including physical design engine and interface design.